2011
DOI: 10.1007/s00023-011-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

On Stable Self-Similar Blow up for Equivariant Wave Maps: The Linearized Problem

Abstract: Abstract. We consider co-rotational wave maps from (3 + 1) Minkowski space into the threesphere. This is an energy supercritical model which is known to exhibit finite time blow up via self-similar solutions. The ground state self-similar solution f0 is known in closed form and based on numerics, it is supposed to describe the generic blow up behavior of the system. In this paper we develop a rigorous linear perturbation theory around f0. This is an indispensable prerequisite for the study of nonlinear stabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 49 publications
2
72
0
Order By: Relevance
“…Furthermore, in [10] it is rigorously proved that λ = 1 is the only eigenvalue with Reλ ≥ 1 and in [9] we show that there do not exist real unstable eigenvalues (except λ = 1). Finally, in [12] it is shown that λ = 1 is the only eigenvalue with real part greater than 1 2 . All these results leave no doubt that ψ T is indeed mode stable although a completely rigorous proof of this property is still not available.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Furthermore, in [10] it is rigorously proved that λ = 1 is the only eigenvalue with Reλ ≥ 1 and in [9] we show that there do not exist real unstable eigenvalues (except λ = 1). Finally, in [12] it is shown that λ = 1 is the only eigenvalue with real part greater than 1 2 . All these results leave no doubt that ψ T is indeed mode stable although a completely rigorous proof of this property is still not available.…”
Section: Introductionmentioning
confidence: 94%
“…If the latter is true, then how does the breakdown (blow up) occur? There exists a heuristic principle which gives a hint for scaling invariant equations that possess a positive energy (such as the wave maps equation, see [12]). If the scaling behavior is such that shrinking of the solution is energetically favorable, then one expects finite time blow up.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations